Assessment of Food Safety Knowledge, Attitude, Self-Reported Practices, and Microbiological Hand Hygiene of Food Handlers - Lee, H.K.; Abdul Halim, H.; Thong, Kwai Lin; Chai, L.C. (MDPI, 2017)
Institutional foodborne illness outbreaks continue to hit the headlines in the country, indicating the failure of food handlers to adhere to safe practices during food preparation. Thus, this study aimed to compare the knowledge, attitude, and self-reported practices (KAP) of food safety assessment and microbiological assessment of food handlers’ hands as an indicator of hygiene practices in food premises. This study involved 85 food handlers working in a university located in Kuala Lumpur, Malaysia. The food safety KAP among food handlers (n = 67) was assessed using a questionnaire; while the hand swabs (n = 85) were tested for the total aerobic count, coliforms, and Escherichia coli, Staphylococcus aureus, Salmonella, Vibrio cholerae and Vibrio parahaemolyticus. The food handlers had moderate levels of food safety knowledge (61.7%) with good attitude (51.9/60) and self-reported practices (53.2/60). It is noteworthy that the good self-reported practices were not reflected in the microbiological assessment of food handlers’ hands, in which 65% of the food handlers examined had a total aerobic count ≥20 CFU/cm2 and Salmonella was detected on 48% of the food handlers’ hands. In conclusion, the suggestion of this study was that the food handlers had adequate food safety knowledge, but perceived knowledge failed to be translated into practices at work.